(untitled) (College of Basic Education Research Journal, 2025)
Patronage is one of key elements that affecting translator and translation simultaneously. It presents powers (people, institutions) that can help or hinder reading, writing, and rewriting of literature. This study aims to demonstrate influence of news agency patrons on translating political speech, and translation in political media which is used for attitudinal manipulation, affecting readers’ ability to make up their own opinions, as well as revealing double standards of news agencies and how they appear in translation. The study hypothesizes that attitudes of news agencies could be changed due to street developments, social media pressures, or recipient expectations, which reflect that news agency patrons influence political discourse translation. Concerning data collection: four political texts related to current Palestinian-Israeli conflict, specifically 2 texts about the 7th October day (Al-aqsa Flood operation launch), and other 2 after that (Al-Ahli hospital massacre, and the flour massacre) have been taken from three Arabic News agencies: Al-Jazeera, Al-Arabiya, and Sky News. Source texts have been analysed using text-typology of Basil Hatim (1997). Target texts are analysed according to Managing and Monitoring Shunnaq’s translation model (1992). Study concludes that percentage of monitoring has exceeded managing at day of Al-Aqsa Flood operation, which indicates that translator at that time monitors text somehow with a slight managing. Whereas after Al-Aqsa Flood operation, translator manages text with a slight monitoring, in accordance with regulations of news agency’s patrons who are affected by external pressures or impacts to align with target audience.